Headache and seizure on postpartum day 7: late postpartum eclampsia: a case report - Raj, Aman Deep; Dixit, Abhinav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Historically, convulsions beginning more than 48 hours, but less than 4 weeks, after delivery, known as late postpartum eclampsia, was thought to be uncommon; however, recent evidence suggests that its incidence is increasing. In addition, the presentation of late postpartum preeclampsia-eclampsia may differ from that occurring during the pregnancy. About 40% of late eclampsia has no premonitory symptoms. This contributes to difficulty in diagnosing late postpartum preeclampsia-eclampsia in an emergency department setting. Greater awareness and knowledge of this disorder by ED physicians should improve outcomes in these potentially life-threatening cases. The authors present a case of new-onset seizures occurring 07 days postpartum. The patient presented with headache, hypertension, and generalized tonic-clonic seizures to the emergency department. Postpartum eclampsia was diagnosed and IV magnesium sulphate was administered. The patient had no further seizures and did not require long-term anticonvulsants.